2021
DOI: 10.3892/ijmm.2021.5056
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies targeting Wnt/β‑catenin signaling for colorectal cancer (Review)

Abstract: colorectal cancer (cRc) is one of the most common carcinomas. Although great progress has been made in recent years, cRc survival remains unsatisfactory due to high metastasis and recurrence. Understanding the underlying molecular mechanisms of cRc tumorigenesis and metastasis has become increasingly important. Recently, aberrant Wnt/β-catenin signaling has been reported to be strongly associated with cRc tumorigenesis, metastasis and recurrence. Therefore, the Wnt/β-catenin signaling pathway has potential val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 176 publications
(357 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, all five patients with APC mutations had other concurrent gene mutations ( TP53 or KRAS ). CTNNB1 mutations have been shown to closely associate with activation of the Wnt pathway as well as APC mutations [ 28 ]. The CTNNB1 mutation rates were 13.6% in SBA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all five patients with APC mutations had other concurrent gene mutations ( TP53 or KRAS ). CTNNB1 mutations have been shown to closely associate with activation of the Wnt pathway as well as APC mutations [ 28 ]. The CTNNB1 mutation rates were 13.6% in SBA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding regulatory function, previous literature reported that the WNT signaling pathway is the main pathway that promotes CRC stemness (39). Tang et al revealed that TM4SF1 is a key gene in CRC recurrence and metastasis and promotes CRC stemness through the WNT signaling pathway (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent investigations on cancer stem cells are focused on examining the molecular mechanisms responsible for Wnt signaling in Apc and β-catenin mutated colorectal cancer cell organoids [ 61 , 62 , 63 , 64 , 65 ], the role of DNA repair in stem cell renewal [ 66 ], mechanisms for regulation of CD44 in stem cell proliferation [ 67 ], the role of one-carbon metabolism in cancer stem cells [ 68 ], and the role of ER-β in mammary carcinogenesis [ 69 ]. The Wnt/β-catenin signaling pathway plays important roles in colon cancer metastasis, cancer stem cell biology and epithelial-mesenchymal transition process, and therefore, a valuable therapeutic target [ 70 , 71 ]. Retinoic acid receptor agonists may function as novel inhibitors of colon cancer progression [ 72 ].…”
Section: Future Prospectsmentioning
confidence: 99%